(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The island type of a dialect of a regional language can be a favourable factor of development, which makes the dialect in question more «successful» than the other varieties of the same idiom spoken on the mainland. In the domain of Scots, Ullans (Ulster Scots) proved to be its most «successful» variety, which has enjoyed favourable conditions for development since the late twentieth century. The Shetland dialect, as a vital variety having important differential features and performing a symbolic function in the community, also has a significant potential for development if the situation favours it. Keywords: linguistic island, island dialect, resettlement dialect, regional language, sustainable development. DOI 10.18522/1995-0640-2020-1-111-122